Restless secularism : modernism and the religious inheritance - Mutter, Matthew (Yale University Press, 2017)
A scholarly and deeply sensitive study that explores how religion and secularism are tightly interwoven in the major works of modernist literature Matthew Mutter provides a broad survey of modernist literature, examining key works against a background of philosophy, theology, intellectual and social history, while tracing the relationship of modernism's secular imagination to the religious cultures that both preceded and shaped it. Mutter's provocative study demonstrates how, despite their explicit desire to purify secular life of its religious residues, Wallace Stevens, Virginia Woolf, and other literary modernists consistently found themselves entangled in the religious legacies they disavowed